Herpesviruses, as a possible cause complicated course of invasive meningococcal disease (clinical case) - N. V. Skripchenko; A. A. Vilnits; A. S. Drap; I. A. Ivashchenko (Журнал инфектологии)
The article describes the clinical case of meningococcal infections, complicated with the development of reactive arthritis. It highlights possible pathogenetic mechanisms of aseptic inflammation in combined meningococcal and herpesvirus infections. The role of herpesviruses as a co-factor in the formation of unfavorable course of meningococcal infection. The effectiveness of antiherpetic therapy in the complex treatment of meningococcal disease.